2010
DOI: 10.1021/ml100062z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the c-Kit Promoter G-quadruplexes with 6-Substituted Indenoisoquinolines

Abstract: Herein, we demonstrate the design, synthesis, biophysical properties, and preliminary biological evaluation of 6-substituted indenoisoquinolines as a new class of G-quadruplex stabilizing small molecule ligands. We have synthesized 6-substituted indenoisoquinolines 1a-e in two steps from commercially available starting materials with excellent yields. The G-quadruplex stabilization potential of indenoisoquinolines 1a-e was evaluated by fluorescence resonance energy transfer-melting analysis, which showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…To date, the research on the small molecule ligands targeting the c-kit gene promoter region attracts more attention. For example it was reported that 6-substituted indenoisoquinoline 51 (Fig. 5A), benzo[α]phenoxazine derivatives 52 (Fig.…”
Section: The C-kit Receptor-targeted Therapiesmentioning
confidence: 99%
“…To date, the research on the small molecule ligands targeting the c-kit gene promoter region attracts more attention. For example it was reported that 6-substituted indenoisoquinoline 51 (Fig. 5A), benzo[α]phenoxazine derivatives 52 (Fig.…”
Section: The C-kit Receptor-targeted Therapiesmentioning
confidence: 99%
“…15,16 These rigid ligands comprise a planar, aromatic core with the capability of stacking on the G-quartet. Some flexible ligands with unfused aromatic scaffolds, such as bisindole carboxamides and diarylethynyl amides, 20,21 are also found to bind to the c-KIT G-quadruplex DNA in vitro.…”
Section: −9mentioning
confidence: 99%
“…14,15 The unfused aromatic ring system seems too feasible and nonplanar to effectively stack on the G-quartet and stabilize the G-quadurplex DNA. In addition, Figure 2.…”
Section: −9mentioning
confidence: 99%
“…In theory, oncogenes associated with all six hallmarks of cancer (Hanahan and Weinberg, 2011) can be targeted with G-quadruplex ligands. G-quadruplex ligands can inhibit c-kit expression and activity in a c-kitexpressing gastrointestinal stromal tumor cell line (Gunaratnam et al, 2009;Bejugam et al, 2010;McLuckie et al, 2011). The G-quadruplex ligand quarfloxin decreases RNA polymerase I transcription by inhibiting nucleolin binding to ribosomal DNA G-quadruplexes in the nucleoli (Drygin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%